Does greenwashing create value of the firm? The moderating role of political connection - Aryo Bimo Setya Permana; Ika Pratiwi (Proceeding International Conference on Accounting and Finance, 2026)
This study examines the relationship between greenwashing and firm value, along with the moderating role of political connections, using a sample of 28 non-loss firms from the Indonesia Stock Exchange LQ45 index from 2020 to 2024 making 140 firm year observations. Framed within stakeholder theory, the research hypothesizes that greenwashing negatively affects firm value and that political connections enhance firm value and weaken the negative effect of greenwashing. The results, based on a Moderated Ordinary Least Square (OLS) model, indicate that greenwashing is not statistically significant in explaining firm value. Surprisingly, political connection is found to negatively affect firm value. Crucially, the interaction term of greenwashing and CEO political conncetion is also not significant, indicating that CEO political connection does not moderate the relationship. This non-significant impact of greenwashing contradicts much of the international literature and suggests that, in the Indonesian context, stakeholders may face challenges in verifying environmental claims, allowing firms to avoid immediate short-term financial penalties. The study highlights a potential regulatory gap, emphasizing the need for policymakers to mandate stricter environmental disclosure and transparency.